Stroke recurrence in the different subtypes of ischemic stroke. The importance of the intracranial disease - Marcos C Lange; Gustavo Ribas; Valeria Scavasine; Renata Dal-Prá Ducci; Danielle C. Mendes; Viviane de Hiroki Flumignan Zétola; Norberto Cabral; Tatjana Rundek (Arquivos de Neuro-Psiquiatria)
ABSTRACT The aim of the study was to analyze the long-term recurrence rate in patients with a first-ever ischemic stroke secondary to intracranial large artery atherosclerosis (LAA) in a Brazilian population. Methods: All stroke patients admitted to the hospital between October 2012 and September 2015 were evaluated. The stroke mechanism subtypes were classified as cardioembolism, LAA, small-vessel occlusion, other determined etiologies, and stroke of undetermined etiology. Results: The 359 first-ever ischemic stroke patients were followed up for a mean time of 21.6 ± 15.1 months. The LAA intracranial (38.9%) and extracranial (24.6%) stroke patients presented with a higher stroke recurrence. Intracranial LAA [HR, 10.2 (3.6–29.1); p < 0.001] and extracranial LAA [HR, 5.05 (1.79–14.2); p = 0.002] were the only conditions to show positive correlation with the recurrence rate, after adjusting for risk factors, thrombolysis, and National Institutes of Health Stroke Scale score at admission. Conclusion: Intracranial LAA presents a higher incidence of recurrence of ischemic stroke when compared with other etiologies in a Southern Brazilian population.